Initiation of Low-threshold Buprenorphine in Nontreatment Seeking Patients With Opioid Use Disorder Engaged in Hepatitis C Treatment. Issue 1 (January 2022) - Hill, Kristi; Nussdorf, Laura; Mount, Julia D.; Silk, Rachel; Gross, Chloe; Sternberg, David; Bijole, Phyllis; Jones, Miriam; Kier, Randy; Mccullough, Dana; Mathur, Poonam; Kottilil, Shyam; et al.
Abstract : Objective: The ANCHOR program offered buprenorphine treatment to people who inject drugs engaged in hepatitis C (HCV) treatment at a Washington, DC harm reduction organization. This analysis describes the program model and outcomes of the opioid care continuum at 1 year. Methods: Primary outcomes were initiation of buprenorphine and retention in care, defined by an active buprenorphine prescription at given time points. Secondary outcomes included treatment interruptions, reasons for treatment noninitiation and termination, buprenorphine and opiate use, and HIV risk behaviors. Buprenorphine and opiate use were measured by urine toxicology screens and HIV risk behavior was quantified using a validated survey. Results: Of 67 patients receiving HCV treatment not on opioid agonist therapy at baseline, 96% (n = 64) were interested and 73% (n = 49) initiated buprenorphine. Retention was 82% (n = 40), 65% (n = 32), and 59% (n = 29) at months 1, 6, and 12, respectively. Retention at 12 months was associated with self-reported engagement in routine medical care ( P < 0.01), but was not associated with gender, stable housing, past opioid agonist therapy, or past overdose. Among retained patients, urine screens positive for opioids were 73% (n = 29), 56% (n = 18), and 79% (n = 23) at months 1, 6, and 12. There was a significant mean decrease in HIV risk-taking behavior scores over the treatment period, primarily driven by reduced injection frequency. Conclusions: Patients engaged in HCV treatment at a harm reduction organization showed a high rate of initiation of buprenorphine treatment, with retention comparable to other treatment settings. Although most patients continued using opioids on treatment, there was a reduced frequency of injection drug use, a significant driver of OUD-related risk. These data support the use of low-threshold buprenorphine access alongside HCV treatment to reduce morbidity and mortality in people with OUD.